Changes In Muhammadiyah’s Fajr Prayer Time Criteria: The Struggle Between Science and Religion - Fitra, Tasnim Rahman; Yusuf, Umar; Hanifa, Fauziyya (Islam Realitas: Journal of Islamic and Social Studies, 2024)
This article explains the science-religion struggle regarding the change in Muhammadiyah's dawn prayer time criteria, where this decision appears to be inconsistent with the research results of three previously appointed institutions. This research falls into the qualitative category, utilizing literature reviews related to the changes in Muhammadiyah's Fajr time criteria. The theory of science-religion relations is employed to dissect how the science-religion struggle is manifested in this decision. In practice, other research, philological studies, and the application in other Muslim countries also contribute to the considerations. The science-religion struggle in Muhammadiyah's decision is classified as an integrative typology in Ian Barbour's theory of science-religion relations. However, as an organization, Muhammadiyah is bound by rules to achieve its goals, guided by the Manhaj Tarjih and maslahah.  Although not explicitly neglecting the scientific aspect, setting -18° as the new criterion for Fajr time indicates Muhammadiyah's inconsistency in applying the research results of its three competent internal institutions. Artikel ini menjelaskan tentang pergumulan sains-agama dalam hal perubahan kriteria waktu subuh Muhammadiyah, dimana ketetapan ini terlihat tidak sesuai dengan hasil penelitian 3 lembaga yang telah ditunjuk sebelumnya. Penelitian ini tergolong pada penelitian kualitatif dengan menggunakan kajian kepustakaan terkait dengan perubahan kriteria waktu subuh Muhammadiyah. Teori relasi sains-agama digunakan untuk membedah bagaimana pergumulan sains-agama dalam keputusan ini. Pada prakteknya, penelitian lain oleh kader Muhammadiyah, kajian Filologi, dan penerapan pada negara muslim lain. Pergulatan sains-agama dalam keputusan Muhammadiyah ini tergolong tipologi integrasi dalam teori relasi sains-agama Ian Barbour, namun sebagai sebuah organisasi Muhammadiyah memiliki keterikatan terhadap aturan dalam pencapaian tujuan, dalam hal ini berpedoman kepada manhaj Tarjih dan kemaslahatan. Walaupun tidak serta merta sebagai pengabaian terhadap aspek sains, namun penetapan angka -18° sebagai kriteria baru waktu subuh menunjukkan ketidakkonsistenan Muhammadiyah dalam menerapkan hasil penelitian 3 lembaga internalnya yang berkompeten.